Analysis of the short-term temporal variation of differential code bias in GNSS receiver. (1st March 2020) - Liu, Ang; Li, Zishen; Wang, Ningbo; Yuan, Chao; Yuan, Hong
Highlights: The stability of RDCB is related to the receiver type, regardless of antenna type. A strong correlation (up to 0.94) between RDCB and satellites Doppler was observed. 15 degrees are the most favorable for the stability of RDCB. Abstract: The short-term variation of GNSS Receiver Differential Code Biases (RDCB) has become one of the main error sources affecting the retrieval of ionospheric Total Electron Content (TEC). In this paper, the Modified Carrier-to-Code Leveling and its simplified method are used to analyze the RDCB variation characteristics under real and simulation conditions, respectively. The results under simulation conditions show that the receiver types have an obvious impact on the stability of RDCB within 0.5 ns. In contrast, the antenna has little effect. Moreover, a strong correlation between the variation of RDCB and the satellites Doppler shift has been observed. Moreover, the ambient temperature significantly affects the RDCB, and 15 degrees is the most favorable for the stability of RDCB, which is 30–85% higher than other temperature conditions. Additionally, the analysis results under real condition indicate that about 4–10% of the International GNSS Service (IGS) station receivers have significant daily variation in RDCB.